Трансформація готичної літературної традиції в сучасному романі США - Нагчевська, Олена Олександрівна (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті простежуються основні тенденції розвитку готичної традиції в літературі США, визначаються константи поетики готичного роману: готичний хронотоп (замковий), лейтмотиви родинного прокляття, розпаду родинних зв’язків, утечі, переслідування, руйнування. Обґрунтовується поява «неоготичного» наративу й досліджуються його основні риси на прикладі аналізу творчості американської письменниці Джойс Керол Оутс.The article deals with the main tendencies in the development of gothic literary tradition in the USA. The author researches the literary and art criticism on this phenomenon and determines the significant role of the gothic tradition in the process of forming the national American literature, marks out the principle elements of preromantic and romantic poetics of the gothic novel which characterize the creative works of American writers, such as chronotop, family curse, pursuit, escape, counteracts, metaimages of labyrinth, vaults, crypts, etc. The gothic tradition is determined as established historic and literary phenomenon created at the turn of the XVIIIthXIXth centuries. The phenomenon of American «neogothic» is described and the principle features of the «new gothic», «neogothic» or «postgothic fiction» established at the turn of the XXthXXIst centuries are given: the creative rethinking and parody of genre dominants, stereotypes and clichés of the gothic literature, different types of intertexual ties with classical genre models, complexity of space and time structures and narrative models, emphasis on the critical psychological situations of a man.
Keywords: готична традиція; трансформація готичної традиції; романтичний роман «romance»; постготична проза; неоготика